Autre côté de la maternité : témoignages recueillis par Viviane Berthommier, Annie Ferrey-Martin, Catherine Wolf. - Berthommier, Viviane (Paris : Maspero, 1974)
Fonds Emilienne Brunfaut
Frans
Monografie